Latent heterogeneity of deviant behaviors and associated factors among ethnic minority adolescents: a latent class analysis - Kunjie Cui; Ted C. T. Fong; Paul Siu Fai Yip (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Background Deviant behaviors are common during adolescence. Despite the diversity of juvenile delinquency, the patterns of deviant behaviors remain unclear in ethnic minorities. The present study aimed to evaluate the latent heterogeneity of deviant behaviors and associated factors in ethnic minority Yi adolescents. Methods The present study recruited a large sample of 1931 ethnic minority Yi adolescents (53.4% females, mean age = 14.7 years, SD 1.10) in five secondary schools in 2022 in Sichuan, China. The participants completed measures on 13 deviant behaviors and demographic characteristics, attitudinal self-control, and psychological distress. Sample heterogeneity of deviant behaviors was analyzed via latent class analysis using class as the cluster variable. Results The data supported three latent classes with measurement invariance by sex. 68.2%, 28.0%, and 3.8% of the sample were in the Normative, Borderline, and Deviant class, with minimal, occasional, and extensive deviant behaviors, respectively. The Deviant class was more prevalent in males (6.5%) than females (1.6%). There were significant class differences in domestic violence, school belonging, self-control, anxiety, and depressive symptoms. Males, domestic violence, low school belonging, and impaired self-control significantly predicted higher odds of the Deviant and Borderline classes compared to the normative class. Conclusion This study provided the first results on three latent classes of deviant behaviors with distinct profiles in ethnic minority adolescents in rural China. These results have practical implications to formulate targeted interventions to improve the psycho-behavioral functioning of the at-risk adolescents in ethnic minorities.